Navigating infection by pathogenic spirochetes: The host-bacteria interface at the atomic level - Hejduk, Libor; Müller, Norbert; Rathner, Adriana; Štěrba, Ján; Hung, Shang-Cheng; Chyan, Chia-Lin; Rego, Ryan O M; Strnad, Martin (Protein science, 2025)
Pathogenic spirochetes bind and interact with various host structures and molecules throughout the course of infection. By utilizing their outer surface molecules, spirochetes can effectively modulate their dissemination, interact with immune system regulators, and select specific destination niches within the host. The three-dimensional structures of multiple spirochetal surface proteins have been elucidated, providing insight into their modus operandi. This review focuses on the structural characteristics of these sticky molecules and their functional implications, highlighting how these features contribute to the pathogenicity of spirochetes and their ability to persist in the host and vector environments. Recognizing the structural motifs and ligands to which these important virulence determinants bind could open new avenues for developing strategies to block colonization by spirochetal pathogens.
Keywords: spirochetes; Spirochaetales; Protein Structure, Tertiary; bakteriální proteiny; Spirochaetales Infections; Bacterial Proteins; terciární struktura proteinů; lidé; lipoproteins; membránové proteiny; Treponema; Ligands; infection; Humans; adhesins; interakce mikroorganismu a hostitele; atomic structure; nuclear magnetic resonance; Host Microbial Interactions; spirochetové infekce; Membrane Proteins; Leptospira; x‐ray crystallography; ligandy; Borrelia